Pathophysiology of thromboembolism in patients with COVID-19 - Vityala, Yethindra; Krishna, Abhijit; Pandla, Dinesh; Priya Kanteti, Krishna; Sadhu, Jahnavi; Boddeti, Harsha Vardhan; Kintali, Tejesh; Khalid, Mohammad Shaour (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. A small number of critically ill patients with coronavirus disease (COVID-19) develop thromboembolism (arterial or venous), both micro- and macrovascular complications such as deep vein thrombosis, pulmonary embolism, and pulmonary arterial thrombosis. The objective of the study is to describe the pathophysiology of venous thromboembolism in patients with COVID-19. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In this article a narrative review regarding pathophysiology of thromboembolism in patients with COVID-19. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The development of coagulopathy is a consequence of the intense inflammatory response associated with hypercoagulability, platelet activation, and endothelial dysfunction. The pathophysiology that relates pulmonary thromboembolism (PTE) with COVID-19 is associated with a hypercoagulable state. PTE is suspected in hospitalized patients presenting dyspnea, decreased oxygen requirement, hemodynamic instability, and dissociation between hemodynamic and respiratory changes. In COVID-19-associated coagulopathy, initially, patients present with elevated levels of fibrinogen and D-dimer, with minimal changes in prothrombin time and platelet count. The main risk factor for the development of pulmonary embolism is the increase in D-dimer that is associated with the development of PTE. The administration of iodine-based contrast agent to patients with COVID-19 would affect P-creatinine and renal function, where Ultrasound is viewed as cost-effective and highly portable, can be performed at the bedside. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Acute respiratory distress syndrome severity in patients with COVID-19 can explain PTE as a consequence of an exaggerated immune response.